Stem radiofrequency monoablation in the treatment of decompensated forms of varicose veins of the lower extremities - Kutovyi, O. B.; Sokolov, O. V. (Medicni Perspektivi, 2020)
Main recommendations in treatment of decompensated forms of varicose veins of the lower extremities, accompanied with the formation of trophic ulcers (stage C6 according to CEAP classification) are the use of compression therapy and various surgical procedures. In this case, the way of choosing a treatment tactic, taking into account the characteristics of venous circulation in the limbs, remains to be incomplete in every single case. The aim of the work is comparative evaluation of the results of using radiofrequency (RF) ablation of the trunk of the saphenous vein in patients with varicose veins of the lower extremities in stage C6, provided that pathologically altered tributaries are preserved or removed. The study included 59 patients with varicose veins of the lower extremities in stage C6, with reflux in the large saphenous vein pool. The total number of men was 17 (28.8%), women – 52 (71.2%). The age of patients ranged from 44 to 87 years (mean age 59.9±7.9 years). The average area of trophic ulcers was 9.6±5.7 cm2. During analysis of postoperative complications on day 7, hematomas and ecchymoses appeared in 29 (96.7%) patients of group I and only in 8 (27.6%) patients of group II. 1 month after the operation, hematoma residues were observed in 3 patients (10%) of I group and were absent in patients of II group. Also, in the postoperative period (day 7 and 1 month), we observed neuropathy phenomena in 3 (10.0%) patients of I group and 1 (3.45%) of a patient of II group. At the end of the follow-up period (6 months), neuropathy phenomena persisted in 2 (6.7%) patients of 1 group, while they were absent in patients of II group. During the first month after surgery, patients showed a significant decrease in leg swelling by 2.4% in I group and by 3.9% in II group. 1 month after the initial intervention, residual varicose-deformed inflows appeared in 5 patients (16.7%) of I group, and in 12 patients (41.4%) of II group (p<0.005). Relapse of an ulcer 6 months after surgery was detected in 2 (6.7%) patients of I group. Comparative results of stem RF monoablation and combined surgery using miniphlebectomy were comparable in terms of the degree of elimination of vertical reflux, reducing the severity of CVI (chronic vein insufficiency, the number of relapses of varicose veins, the healing speed and the frequency of relapse of trophic ulcers. Moreover, the performance of RF monoablation was accompanied by a significant reduction in the volume of drugs for local anesthesia, leading to a more significant decrease in the intensity of pain after surgery, the number of complications, in particular neuropathy, and to improvement in the quality of life. The number of additional sources of pathological horizontal reflux along incomprtent perforating veins and residual varicose-deformed tributaries after surgery requiring corrective interventions were comparable in both groups. Thus, the presence of horizontal reflux is not critical when choosing the method of primary surgical intervention.